2010
DOI: 10.3892/ijo_00000769
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide inactivates Akt and induces caspase-dependent death in cervical cancer cells via the mitochondrial pathway

Abstract: Abstract. Triptolide, the main active component of the traditional Chinese herbal medicine Tripterygium wilfordii Hook F, has been shown to have potent immunosuppressive and anti-inflammatory properties. Here, we investigated the pro-apoptotic effect of triptolide in human cervical cancer cells and its underlying mechanisms. Exposure of cervical cancer cells to triptolide induced apoptosis, which was accompanied by loss of mitochondrial membrane potential, caspase processing (caspase-8, -9 and -3), and cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…Triptolide inhibits cell growth in variety of tumor cells (15,16). In this study, human monocytic leukemia THP-1 cells that had been PMA-differentiated showed inhibition of cell proliferation after triptolide treatment, in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Triptolide inhibits cell growth in variety of tumor cells (15,16). In this study, human monocytic leukemia THP-1 cells that had been PMA-differentiated showed inhibition of cell proliferation after triptolide treatment, in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 58%
“…Triptolide has also been reported to induce significant apoptosis and minor accumulation in the S phase in THP-1 cells (17). However, treatment with triptolide was shown to reduce the viability of HeLa and Caski cells in a concentration-dependent manner and to increase accumulation of sub-G1 phase cells and apoptotic bodies (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, curcumin (Yu et al, 2011;Li et al, 2013;Zhou et al, 2013;Yin et al, 2013) and triptolide (Kim et al, 2010;Liu et al, 2012;Wen et al, 2012) are able to potently inhibit the growth of human cancer cells in vitro and prevents tumor growth in vivo via inhibiting cell proliferation and inducing apoptosis. However, both of curcumin and triptolide possess side effects in high concentration (Banjerdpongchai et al, 2005;Clawson et al, 2010;Antonoff et al, 2010;Li et al, 2010;Borja-Cacho et al, 2010;Shakibaei et al, 2013;Du et al, 2013;Jiang et al, 2013).…”
Section: Combined Effects Of Curcumin and Triptolide On An Ovarian Camentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Moreover, Triptolide proapoptotic and antiproliferative activity has also been associated with a numerous cancer cell lines in vitro and in vivo such as: HL-60, T cell lymphoma (Jurkat), U937, OCI-AML3 Kasumi-1 and SKNO-1 cells, human hepatocellular carcinoma SMMC-7721 cells, and cell lines of multiple myeloma, breast, gastric, prostate, lung, oral, colon, pancreatic and cervical cancers, cholangiocarcinoma, and neuroblastoma. [8][9][10][11][12][13][14][15] In vivo trials confirmed the therapeutic activity of Triptolide in a number of model systems including hamster models, human melanoma xenografts, gastric carcinoma, breast cancer, pancreatic cancer, bladder cancer and neuroblastoma in nude mice studies. [16,18] Moreover, Triptolide has been shown to fortify other agents helping as combination with other drugs to improve their cancer treatment abilities.…”
Section: Introductionmentioning
confidence: 99%